Customer Satisfaction and Loyalty for Online Food Services Provider in India: An Empirical Study - Anand Prasad Sinha; Praveen Srivastava
In the food sector, customers have been voting by their feet since ages. However, due to the technological changes clubbed with present COVID-19 pandemic, the trend has changed rapidly. Customers are confined to their home and technology has emerged as the only saviour. The number of increased downloads of food ordering app is an indication of both popularity of these apps and helplessness of the present age customer. With restricted movement, they have these apps to either get the food delivered at their doorstep or take away with pre-orders. Hence, it becomes imperative for the app designer and food service provider to brainstorm and develop an app which can focus on the customer ease rather than forcing their design and interface to customer. In this backdrop, this study is a novel attempt which primarily focuses on relationship amid customer satisfaction and app quality. The inter-related relationship among service quality, satisfaction of customer and their loyalty using the app has been explored. Collection of the data used stratified random sampling. A total of 380 usable data have been collected from customers who have been using this app for ordering since last one year.